Protocol for a Randomized Controlled Trial to Enhance Executive Function via Brief Mindfulness Training in Individuals with Internet Gaming Disorder - Zhilin Chen; Jie Ge; Quan Gan; Yu Fu; Zhuangfei Chen (PLoS ONE, 2025)
Background Internet Gaming Disorder (IGD) is characterized by uncontrolled gaming behavior, leading to emotional distress, neglect of academic or life responsibilities, and damage to interpersonal relationships, all of which have serious negative impacts on individuals and society. IGD has been associated with neuropsychological impairments, especially executive function deficits, and emotional difficulties. Mindfulness interventions have been indicated to improve executive functions to varying degrees in individuals with IGD. The purpose of this study is to investigate whether the three subcomponents of executive function (i.e., inhibition, updating, and shifting) are impaired in individuals with internet gaming disorder, as well as to examine the effectiveness of a brief mindfulness intervention on executive function. Methods A total of 82 individuals diagnosed with IGD and 40 non-addicted gamers will be recruited for this study. These participants will be evenly divided into an intervention group and a control group at a ratio of 1:1. The intervention group will undergo a 7-day mindfulness training program focusing on breathing meditation, while the control group will receive progressive muscle relaxation training. Both groups’ outcomes will be assessed at seven different time points. Primary outcome measures will include electroencephalography (EEG) data (band power, functional connectivity, source localization, and N2/P3 amplitudes), behavioral metrics (response times and accuracy from psychological experimental paradigms), physiological indices (specifically heart rate variability), self-reported measures (game craving and mindfulness levels, executive function performance, and impulsivity emphasizing inhibitory control). Secondary outcome measures will encompass anxiety, stress, positive and negative affect, sleep quality, and other indicators such as demographic information, physical and mental health status, and the Big Five personality traits. Discussion This study aims to explore the efficacy of a brief mindfulness intervention on executive function impairments in IGD individuals and to elucidate its underlying neural mechanisms. It is anticipated that the findings will contribute to more targeted intervention strategies for executive function research, offering novel insights into the treatment of IGD and related cognitive dysfunctions. This study is expected to explore the effectiveness of brief mindfulness intervention on IGD and its underlying brain functional mechanisms, particularly providing more targeted intervention strategies for improving executive functions in this population. Trial registration Trial registration number: ChiCTR2400081509, registered on March 4th 2024. Protocol Version1.0.